Intraoperative Lung-Protective Ventilation Trends and Practice Patterns: A Report from the Multicenter Perioperative Outcomes Group. (November 2015) - Bender, S. Patrick; Paganelli, William C.; Gerety, Lyle P.; Tharp, William G.; Shanks, Amy M.; Housey, Michelle; Blank, Randal S.; Colquhoun, Douglas A.; Fernandez-Bustamante, Ana; Jameson, Leslie C.; Kheterpal, Sachin
Abstract : BACKGROUND: The use of an intraoperative lung-protective ventilation strategy through tidal volume (TV) size reduction and positive end-expiratory pressure (PEEP) has been increasingly investigated. In this article, we describe the current intraoperative lung-protective ventilation practice patterns and trends. METHODS: By using the Multicenter Perioperative Outcomes Group database, we identified all general endotracheal anesthetics from January 2008 through December 2013 at 10 institutions. The following data were calculated: (1) percentage of patients receiving TV > 10 mL/kg predicted body weight (PBW); (2) median initial and overall TV in mL/kg PBW and; (3) percentage of patients receiving PEEP ≥ 5 cm H2 O. The data were analyzed at 3-month intervals. Interinstitutional variability was assessed. RESULTS: A total of 330, 823 patients met our inclusion criteria for this study. During the study period, the percentage of patients receiving TV > 10 mL/kg PBW was reduced for all patients (26% to 14%) and in the subpopulations of obese (41% to 25%), short stature (52% to 36%), and females (39% to 24%; all P values <0.001). There was a significant reduction in TV size (8.90–8.20 mL/kg PBW, P < 0.001). There was also a statistically significant but clinically irrelevant difference between initial and overall TV size (8.65 vs 8.63 mL/kg PBW, P < 0.001). Use of PEEP ≥ 5 cm H2 O increased during the study period (25%–45%, P < 0.001). TV usage showed significant interinstitutional variability ( P < 0.001). CONCLUSIONS: Although decreasing, a significant percentage of patients are ventilated with TV > 10 mL/kg PBW, especially if they are female, obese, or of short stature. The use of PEEP ≥ 5 cm H2 O has increased significantly. Creating awareness of contemporary practice patterns and demonstrating the efficacy of lung-protective ventilation are still needed to optimize intraoperative ventilation. Abstract : Published ahead of print September 1, 2015